An evaluation of teachers opinions about the servant leadership behaviours of school principals: A critical review - Kandasamy, Silllalee S.; Muniandy, Rajantheran; Kandasamy, Matana; Mutty, Bharathi; Samuel, Samikkanu Jabamoney Ishak (Primrose Hall Publishing Group, 2019)
This is a review of 'An Evaluation of Teachers' Opinions about the Servant Leadership Behaviours of School Principals' published in Educational Process: International Journal. That article delves into how school teachers perceive the implementation of the 'Servant Leadership Behaviours' concept by school principals, where teachers serve under these principals' supervision. It also identifies the level of this concept's application in primary and secondary schools. The article has strengths and weaknesses. The concept of servant leadership by school principals is well-explained and it effectively employs methodology (snowball sampling and content analysis). It systematises data, succeeds in answering the research questions, and its references are compatible with bibliographic rules. But the article lacks a research problem statement or review of past studies, has a shallow and unorganised introduction, and only vaguely distinguishes data analysis from its overall conclusion. Finally, the current review identifies the article's positives for readers despite its few weaknesses.. © 2019 Primrose Hall Publishing Group.